State estimation of power system mode parameters by telemetry and synchronized phasor measurements - Batseva, N.L.; Foos, J.A. (Eurasian Physical Technical Journal, 2024)
Real time hardware and software systems are operated at centers of a power system operation. The key unit of these systems is the state estimation block since, based on the results of mode parameters derived from this block, parameters that are more comprehensive can be calculated. These parameters are considered for system stability and reliability. Currently, not only telemetry but also synchronized phasor measurements can be used for a state estimation. Therefore, the development of state estimation methods is the relevant task. The proposed method allows improving the estimation accuracy and the quality of decisions, related to system stability and reliability. The method is based on mathematical frameworks of the Gauss-Newton method and extended Kalman filter, when telemetry and synchronized phasor measurements arrays are used simultaneously. It is confirmed, that the given method increases an accuracy of the voltage and active power flow estimation at steady state and post-accident modes, in contrast to the standard state estimation method. The developed algorithm enables the implementation of this method into the state estimation block of real time hardware and software systems. The upcoming trends for the development of state estimation methods in the event of dynamic processes in power system areas are also formed.
Keywords: state estimation; Gauss-Newton method; extended Kalman filter; telemetry; synchronized phasor measurements